Stem cell therapies for age-related macular degeneration: the past, present, and future - Dang Y (Dove Medical Press, 2015)
Yalong Dang,1–3 Chun Zhang,1,2 Yu Zhu31Department of Ophthalmology, Peking University Third Hospital, Beijing, People’s Republic of China; 2Clinical Stem Cell Research Center, Peking University Third Hospital, Beijing, People’s Republic of China; 3Department of Ophthalmology, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaAbstract: In the developed world, age-related macular degeneration (AMD) is one of the major causes of irreversible blindness in the elderly. Although management of neovascular AMD (wet AMD) has dramatically progressed, there is still no effective treatment for nonneovascular AMD (dry AMD), which is characterized by retinal pigment epithelial (RPE) cell death (or dysfunction) and microenvironmental disruption in the retina. Therefore, RPE replacement and microenvironmental regulation represent viable treatments for dry AMD. Recent advances in cell biology have demonstrated that RPE cells can be easily generated from several cell types (pluripotent stem cells, multipotent stem cells, or even somatic cells) by spontaneous differentiation, coculturing, defined factors or cell reprogramming, respectively. Additionally, in vivo studies also showed that the restoration of visual function could be obtained by transplanting functional RPE cells into the subretinal space of recipient. More importantly, clinical trials approved by the US government have shown promising prospects in RPE transplantation. However, key issues such as implantation techniques, immune rejection, and xeno-free techniques are still needed to be further investigated. This review will summarize recent advances in cell transplantation for dry AMD. The obstacles and prospects in this field will also be discussed.Keywords: stem cell, age-related macular degeneration, retinal pigment epithelium, cell reprogramming, clinical trial